2012
DOI: 10.5127/jep.019711
|View full text |Cite
|
Sign up to set email alerts
|

Friend or Foe? Memory and Expectancy Biases for Faces in Social Anxiety

Abstract: Studies examining memory biases for threat in social anxiety (SA) have yielded mixed results. In the present study, memory and expectancy biases were tested using a novel face recognition paradigm designed to offset methodological challenges that have hampered previous research. Following a social threat induction, undergraduates with high (n = 40) and low (n = 40) levels of SA viewed a series of neutral faces randomly paired with positive or negative social feedback. Recognition memory was tested for previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…On the other hand, studies using facial expressions have yielded mixed results (e.g., Bielak & Moscovitch, 2012;Coles & Heimberg, 2005, Foa, Gilboa-Schechtman, Amir, & Freshman, 2000Lemoult & Joormann, 2012). Differences in methodology could account for these inconsistencies.…”
Section: Long-term Memorymentioning
confidence: 86%
“…On the other hand, studies using facial expressions have yielded mixed results (e.g., Bielak & Moscovitch, 2012;Coles & Heimberg, 2005, Foa, Gilboa-Schechtman, Amir, & Freshman, 2000Lemoult & Joormann, 2012). Differences in methodology could account for these inconsistencies.…”
Section: Long-term Memorymentioning
confidence: 86%
“…Such inconsistency of findings is characteristic of research in this area, with some studies showing evidence of enhanced memory for threatening over neutral material in anxious participants (see for example Cloitre, Shear, Cancienne, & Zeitlin, 1994;Reidy, 2004;Reidy & Richards, 1997a, 1997b and others finding little or no support for a bias of this nature (see for example Bielak, & Moscovitch 2012;Bradley, Mogg, & Williams, 1995;Mathews & MacLeod, 1985;Mogg, Mathews, & Weinman, 1989;Nugent & Mineka, 1994). A meta-analysis on anxiety and memory bias showed a large discrepancy in the effect sizes and even the directionality of the findings in recognitionbased studies (between group effect sizes for hit rates ranged between g = -1.28 and g = 1.27; Mitte, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Yet evidence of negative memory bias in SA is mixed, prompting a need for clearer identification of the conditions in which it does and does not occur. Several studies have found SA-related memory bias of negative social events that signaled imminent social threat (e.g., Bielak & Moscovitch, 2012; Cody & Teachman, 2010). These studies suggest that memory biases for negative evaluations are especially strong in individuals with SA due to the self-relevant nature of the recalled information.…”
mentioning
confidence: 99%